2017
DOI: 10.1002/btpr.2432
|View full text |Cite
|
Sign up to set email alerts
|

Screening different host cell lines for the dynamic production of measles virus

Abstract: Measles virus (MV) has a natural affinity for cancer cells and oncolytic MV preparations have therefore been investigated in several clinical trials as a potential treatment for cancer. The main bottleneck in the administration of oncolytic MV to cancer patients is the production process, because very large doses of virus particles are required for each treatment. Here, we investigated the productivity of different host cells and found that a high infection efficiency did not necessarily result in high virus y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Michael Muehlebach (Paul-Ehrlich-Institute, Langen, Germany). The dynamic production of MV in suspension was carried out in a stirred-tank reactor [6,8]. Vero cells (CCL-81, ATCC) were grown on 3 g L −1 Cytodex 1 microcarriers (GE Healthcare, Chicago, Illinois, USA) in SCM or SFM.…”
Section: Cell Culture and MV Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Michael Muehlebach (Paul-Ehrlich-Institute, Langen, Germany). The dynamic production of MV in suspension was carried out in a stirred-tank reactor [6,8]. Vero cells (CCL-81, ATCC) were grown on 3 g L −1 Cytodex 1 microcarriers (GE Healthcare, Chicago, Illinois, USA) in SCM or SFM.…”
Section: Cell Culture and MV Propagationmentioning
confidence: 99%
“…Measles virus (MV) is a leading candidate owing to the excellent safety profile of the measles vaccine [2]. However, at least 10 8 infectious MV particles are needed per dose for cancer therapy [3,4] and this has prompted extensive studies focusing on the optimization of upstream processes [5][6][7][8][9][10]. The deeper understanding of MV production gained from these studies has shown that shear stress and aeration play a key role in process productivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-standing experience with the Vero cell line and its acceptance by regulatory authorities, continue to make it the substrate of choice for many vaccine manufacturers ( Barrett et al, 2009 ; Genzel, 2015 ). Moreover, in direct comparison with other cell lines, Vero has shown superior virus productivity for a range of viruses, including dengue virus, enterovirus type 71, Japanese encephalitis virus, measles virus and Peste des Petits ruminants virus ( Grein et al, 2017 ; Liu et al, 2008 ; Silva et al, 2008 ; Wu et al, 2004 ; Wu and Huang, 2000 ). For influenza virus, however, MDCK cells demonstrated superior virus production than Vero cells ( Genzel et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Vero cells are also investigated as cell substrate for the production of certain oncolytic viruses ( Grein et al, 2017 ). In contrast to infectious disease preventing vaccines, viral oncolytic therapy fights cancer by selectively targeting and killing cancer cells through oncolytic virus replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation